The credibility of intermediate hyperglycemia (IH) at one hour of OGTT in 30 β-thalassemia patients (β-thal) with persistent low iron overload - Campisi, Saveria; De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2024)
Background: Intermediate hyperglycemia (IH) at 1-hour during oral glucose tolerance test (OGTT) has received attention as a useful early biomarker of dysglycemia. Objective: The main objective of this study was to gain further insight into IH in 30 β-thalassemia (β-thal) patients with a spectrum of genotypes and persistent low iron load (serum ferritin; SF:<1,000 μg/L), related to effective treatment with oral iron chelation monotherapy. Methods: OGTT was performed according to the American Diabetes Association (ADA) guidelines. Venous blood samples for PG and insulin assays were collected at 0, 60, and 120 minutes after glucose load for PG and insulin assays. Results: Based on the OGTT results, 13 out of 30 patients (43.3%) had normal glucose tolerance (NGT), and 4 out of 32 (12.5%) patients impaired fasting glucose (IFG). Interestingly, isolated IH (i-IH at 1-hour post-OGTT: PG: ≥ 155 mg/dL) and type 2 diabetes mellitus at 1-hour post-OGTT (PG : ≥ 209 mg/dL) were detected in 5 (16.6%) and 3 (10%) out of 30 patients, respectively. IH associated with IFG and impaired glucose tolerance (IGT) was detected in 3 (10%) and 2 (6.6%) out of 30 patients, respectively. β-TDT patients were divided into two subgroups: those with NGT and those with IH. A statistically significant difference between the two groups was observed only for the HOMA 2 - % β index (P = 0.042). Conclusion: Intermediate hyperglycemia at 1-hour during OGTT in β-thal is a sensitive index to identify early glucose dysregulation even in patients with NGT.